Changes in neurovascular coupling with cerebral perfusion pressure indicate a link to cerebral autoregulation. Issue 7 (July 2022) - Acharya, Deepshikha; Ruesch, Alexander; Schmitt, Samantha; Yang, Jason; Smith, Matthew A; Kainerstorfer, Jana M
Cerebral autoregulation ensures a stable average blood supply to brain tissue across steady state cerebral perfusion pressure (CPP) levels. Neurovascular coupling, in turn, relies on sufficient blood flow to meet neuronal demands during activation. These mechanisms break down in pathologies where extreme levels of CPP can cause dysregulation in cerebral blood flow. Here, we experimentally tested the influence of changes in CPP on neurovascular coupling in a hydrocephalus-type non-human primate model (n = 3). We recorded local neural and vascular evoked responses to a checkerboard visual stimulus, non-invasively, using electroencephalography and near-infrared spectroscopy respectively. The evoked signals showed changes in various waveform features in the visual evoked potentials and the hemodynamic responses, with CPP. We further used these signals to fit for a hemodynamic response function (HRF) to describe neurovascular coupling. We estimated n = 26 distinct HRFs at a subset of CPP values ranging from 40–120 mmHg across all subjects. The HRFs, when compared to a subject dependent healthy baseline (CPP 70–90 mmHg) HRF, showed significant changes in shape with increasing CPP (ρCPP  = −0.55, p-valueCPP  = 0.0049). Our study provides preliminary experimental evidence on the relationship between neurovascular coupling and CPP changes, especially when beyond the limits of static autoregulation.